Kemandirian perempuan dalam bingkai kesetaraan dan keadilan gender: Sebuah refleksi naratif Rut dan Naomi - Windarti, Maria Titik (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2023)
The independence, roles, and rights of women who are often discriminated against in many aspects give rise to issues of gender inequality and equality. Through literature study, this research article looks at the Book of Ruth as a canonical book that presents a portrait of independent women from both a humanist and a theocentric perspective that can be used to contribute to strengthening gender inequality. This research found that the figures of Ruth and Naomi, from a humanist perspective, could become models of independent women in terms of religion, work, and homemaking. This research recommends other research related to issues of gender inequality in the global era, especially from a feminist perspective.AbstrakKemandirian, peran, dan hak-hak perempuan yang sering terdiskriminasi dalam banyak segi menimbulkan isu ketidakadilan dan kesetaraan gender. Melalui Studi pustaka, artikel penelitian ini melirik Kitab Rut sebagai kitab kanonik yang menyajikan potret perempuan mandiri baik dari sisi humanis maupun teosentris yang dapat digunakan untuk memberikan sumbangsih bagi penguatan ketidakadilan gender. Hasil penelitian ini menemukan bahwa sosok Rut dan Naomi, dari sisi humanis mampu menjadi model perempuan mandiri dalam hal beragama, bekerja, dan berumahtangga. Penelitian ini merekomendasikan riset lainnya yang berkaitan dengan isu-isu ketidakadilan gender di era global, khususnya dari perspektif feminisme.